Arteriosclerotic Aneurysm of Popliteal Artery - Mazza, Milton E; Calvelo, Agustín; Portos, Ruben; Torterolo, Edgardo (Cirugía del Uruguay, 1980)
Case material comprises 25 patients with 43 arteriosclerotic aneurysms of popliteal artery, studied since 1963. In 72 % ·of patients, aneurysm was bilateral. 22 aneurysms already had complic,Jtions when _the patient first visited the doctor. Most frequent complication was intrasacular thrombosis. AH complicated aneurysms were bilatera'. In the groUp of patients operated fer asymptomatic aneurysm, results were uniformlly good. This was not the case of aneurysms operated because of acute thrombosis, among which we had 3 cases of amputation and 2 deaths. lt is important to operate popliteal aneurysms.